Conflicts In Projects: A Life Cycle Assessment - Shabir Hussain Khahro , Dr. Tauha Hussain Ali, Qasim Hussain Khahro, Fida Hussain Siddique (International Journal of Advanced Science and Technology, 2020)
The construction industry plays a centric role in any countries development. It contributes significantly to the GDP and job market of the country. Construction practitioners aim to finish projects successfully. A project, if planned, designed and constructed in a way that it should meet the project goals and client satisfaction is termed to be successful. Various factors are involved in achieving a successful project and managing conflicts is a key one. This paper aims to investigate the conflict level throughout the life cycle of building sector construction projects. A qualitative survey followed by an SPSS analysis has been made to attain results. The study concludes that most of the conflicts occur in the construction phase of any project followed by the post-construction phase, design phase and pre-design phase. This paper helps the practitioners of this industry to make necessary policies and frameworks to reduce conflicts in building sector construction projects.